Strategic Approach of Reverse Logistics Management for Recyclable Waste and Transportation: A Systematic Review - Pornarit Chounchaisit; Phattranis Suphavarophas; Suphat Bunyarittikit; Piyarat Nanta; Poon Khwansuwan; Panayu Chairatananonda; Wirayut Kuisorn; Chumporn Moorapun (Sustainability, 2025)
Strategic reverse logistics management is a key driver of sustainability in supply chains, where challenges in recyclable waste must be aligned with transportation systems to achieve optimal outcomes. A systematic review using the PRISMA methodology was conducted in December 2024 by searching Scopus, Google Scholar, and Thai Journals Online to examine the global research landscape and the strategic approaches applied in reverse logistics for recyclable waste and transportation. Analysis of 32 publications shows a steady rise in research, with most studies in Asia and dispersed across multiple journals, reflecting the field’s multidisciplinary nature. Four strategic approaches were identified. Model-driven approaches demonstrate strong capability through mathematical, computational, conceptual, and hybrid models, achieving reductions of 44% in climate impacts and 34% in costs. Technology-driven approaches contribute innovations to enhance battery transport safety. Exploratory approaches reveal contextual policy gaps and financial limitations. Hybrid approaches can improve efficiency and reduce CO2 emissions. The future development of hybrid approaches still offers substantial room for broader application and deeper integration. This review supports the development of more effective systems, policies, and future research.
Keywords: Sustainable Supply Chain Management; Municipal Solid Waste Management; Food Waste Reduction and Sustainability